Hub cities in the knowledge economy : seaports, airports, brainports - Conventz, Sven; Derudder, Ben; Thierstein, Alain; Witlox, Frank (Transport and mobility series., 2014)
The overarching research topic addressed in this book is the complex and multifaceted interaction between infrastructural accessibility/connectivity of city-regions on the one hand and knowledge generation in these city-regions on the other hand. To this end, the book brings together chapters analysing how infrastructural accessibility is related to changing patterns of business location of knowledge-intensive industries in city-regions. The chapters in this book specifically dwell on recent manifestations of, and developments in, the accessibility/knowledge-nexus, with a particular ...